Lactobacillus plantarum GX17 benefits growth performance and improves functions of intestinal barrier/intestinal flora among yellow-feathered broilers - Yin, Yangyan; Liao, Yuying; Li, Jun; Pei, Zhe; Wang, Leping; Shi, Yan; Peng, Hongyan; Tan, Yizhou; Li, Changting; Bai, Huili; Ma, Chunxia; Gong, Yu; et al. (Frontiers in Immunology, 2023)
Lactobacillus plantarum has recently been found to be a natural source feed additive bacteria with great advantages in food safety and animal welfare. Discovering novel strains with commercial application potentiation could benefit the local poultry industry, and in particular support Chinese farmers. In this study, we tested a recently isolated novel strain of Lactobacillus plantarum GX17 as a feed additive on the growth performance and intestinal barrier functions of 1-day-old Chinese yellow-feather chicks. As good as other commercial probiotics, feeding with Lactobacillus plantarum GX17 showed significant improvements in humoral immune responses and enhanced the immune effect after vaccination for either the Newcastle disease vaccine or the avian influenza vaccine. This study also found that feeding with Lactobacillus plantarum GX17 improved the feed-to-weight ratio and caused a significant increase of the villus length to crypt depth ratio. Furthermore, Lactobacillus plantarum GX17 significantly up-regulated the mRNA expression of CLDN, MUC2, and TLR2, all of which are jejunum-associated barrier genes, indicating an improvement of the intestinal barrier functions by enhancing the tight junction between epithelia cells. These results are comparable to the effects of feeding the commercial complex probiotics that improve the expression levels of CLDN, ocludin, MUC2, TLR2, and TLR4. In terms of maintaining intestinal health, commercial complex probiotics increased the relative abundance of Parabacteroides and Romboutsia, while Lactobacillus plantarum GX17 increased the relative abundance of Pseudoflavonifractor. Our data suggest that Lactobacillus plantarum GX17 could enhance the intestinal absorption of nutrients and therefore improve the growth performance of Chinese yellow-feather chicks. In conclusion, compared with the commercial complex probiotics, Lactobacillus plantarum GX17 has more positive effects on the growth performance and intestinal barrier function of yellow-feather chickens, and can be used as a feed additive.